Defensive symbionts mediate species coexistence in phytophagous insects. (25th January 2018) - Hertäg, Corinne; Vorburger, Christoph
Abstract: Competition of two species for the same resource is expected to result in competitive exclusion of the inferior competitor. In natural communities, however, other antagonists and symbionts moderate competition. Thus, we have to go beyond studying pairwise interactions. Natural enemies may facilitate coexistence if they affect the superior competitor more strongly, or they can hinder coexistence via apparent competition. Less well studied is the role of symbionts, which may influence species coexistence in conjunction with enemies. Eukaryotes commonly harbour microbial endosymbionts that provide protection against natural enemies, but are costly in their absence. Such defensive symbionts could thus mediate coexistence of species competing for the same resource, both in the presence and in the absence of enemies, but as yet there is little evidence for this claim. We addressed this proposed role of defensive symbionts in replicated simple communities consisting of two aphid species sharing the same host plant and the same natural enemy, a parasitoid wasp. Both, one, or neither species were infected with a resistance‐conferring symbiont, and they competed in the absence as well as the presence of parasitoids. The symbiont had significant effects in the absence of parasitoids by lowering competitive ability especially in one species, but the effects were more dramatic in the presence of parasitoids. With both species protected by the symbiont, parasitoid densities remained low and both aphid species persisted. When neither species was protected, parasitoids drove both species to extinction. Surprisingly, the same outcome was observed when only one species was protected. The susceptible species supported high densities of parasitoids that also killed the resistant aphids via mechanisms other than parasitism, presumably by disturbing them to the point of starvation. This is an intriguing form of apparent competition. Our results demonstrate an important role of defensive symbionts in insect communities through modifying species interactions. This highlights the need for experimental data when studying species coexistence in competitive networks. Furthermore, the observation that a susceptible host can negatively affect a resistant host via a shared parasitoid is an instructive insight for biological control. A plain language summary is available for this article. Abstract : Plain Language Summary